Electrical and electronic principles and technology - Bird, J. O. (Routledge, 2014)
In this book John Bird introduces electrical and electronic principles and technology through examples rather than theory -- enabling students to develop a sound understanding of the knowledge required by technicians in fields such as electrical engineering, electronics and telecommunications. No previous background in engineering is assumed, making this an ideal text for vocational courses at Levels 2 and 3, foundation degrees and introductory courses for undergraduates. Colour layout helps navigation and highlights key learning points, formulae and exercises. Containing 410 worked problems, 540 further problems, 340 multiple-choice questions, 455 short-answer questions, and 7 revision tests with answers online. Real-world situations and engineering examples put the theory into contex